216k views
1 vote
NEEDED ASAP

Joe was given the recursive formula: f(1) = 3, f(n + 1) = f(n) - 7. To find the second term in the sequence, Joe filled in the formula as followed: f(n + 1) = f(n) - 7 then f(n + 1) = f(2) - 7.

He explained since he is finding the second term in the sequence, the n should be replaced by 2.

If he is correct, what are the 2nd, 3rd and 4th terms?

If incorrect, show the correct formula.

User Krym
by
5.1k points

1 Answer

3 votes

f(1) = 4; f(n+1) = f(n) - 1.25

❤️Hello!❤️ f(1) = 4

f(2) = f(1) - 1.25 = 4 - 1.25 = 2.75

f(3) = f(2) - 1.25 = 2.75 - 1.25 = 1.50

f(4) = 1.50 - 1.25 = 0.25

f(5) = 0.25 - 1.25 = -1

f(6) = -1 -1.25 = -2.25

Sequence: 4, 2.75, 1.50, 0.25, -1, -2.25, ... Hope this helps! ↪️ Autumn ↩️

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.